Níveis de proteínas nas dietas de faisões em crescimento - Neto, Manoel Garcia [UNESP]; Junqueira, Otto Mack [UNESP]; Malheiros, Euclides Braga [UNESP] (My University, 1997)
The experiment with pheasants in initial growth phase (1 to 35 days of age), which had as its objective evaluating the nutritional needs of pheasants in the growth phase as to protein levels in the diets, was conducted on a pheasant farm located at Ribeirão Preto, SP, Brazil. Small pheasants were used, which were submitted to isocaloric diets containing 26%, 28% and 30% of crude protein. The experimental design was totally random with four repetitions of 30 birds per parcel, totaling 360 birds. The results showed that a 30% crude protein level should be recommended for pheasants in the growth phase (1 to 35 days of age).

O experimento, com faisões em fase inicial de crescimento (1 a 35 dias de idade), teve o objetivo de avaliar as exigências nutricionais de faisões na fase de crescimento quanto aos níveis de proteína nas dietas; foi conduzido em uma granja localizada em Ribeirão Preto, SP. Foram utilizados faisõezinhos, os quais foram submetidos às dietas isocalóricas contendo 26%, 28% e 30% de proteína bruta. O delineamento experimental foi o inteiramente casualizado, onde foram estudados os efeitos de três níveis de proteína bruta, com quatro repetições de 30 aves por parcela, totalizando 360 aves. Os resultados mostraram que o nível de 30% de proteína bruta deve ser recomendado para faisões em fase de crescimento (1 a 35 dias de idade).
Effect of dietary protein in the diets for growing ringneck pheasants
Keywords: Alimentary ration; Birds; Body weight; Nutrition; Phasianus colchicus; Weight gain; Aves; Phasianidae